The Influence of Visual Attributes in Packaging Design on Generation Z's Dessert Snack Purchasing Decision - Belliza, Azka; Kusumawati, Nurrani (Journal of Consumer Studies and Applied Marketing, 2024)
This research explores the influence of packaging design on the purchasing decisions of Generation Z consumers, focusing on dessert snack products. The primary objective of this study is to evaluate the extent to which each visual element of a product's packaging influences the purchasing decisions of Generation Z consumers. A further aim is to identify specific preferences for each visual element in food packaging design that Generation Z. favors. In order to achieve these objectives, a mixed-methods approach was employed, combining quantitative surveys with 422 respondents and qualitative interviews with 12 participants, all from Generation Z. The results reveal that visual appeal significantly influences purchasing decisions, primarily through the mediating variable of perceived quality. Individual elements such as appealing color combinations and unique typography enhance perceived quality, driving purchasing decisions. Illustrations on the packaging also significantly impact purchase decisions. The choice of packaging material, especially eco-friendly options, positively affects perceived quality, while the shape and size of packaging influence perceptions of practicality and quality. While some visual elements, like product photography and shape, show small influences and do not directly influence purchase decisions, they contribute to the packaging's overall attractiveness and perceived quality. These findings suggest that effective packaging design tailored to the visual preferences of Generation Z can enhance the marketability of dessert snack products. However, the study has limitations, including its focus on a specific product category and demographic group, which may not generalize to other contexts. Future research could explore the influence of packaging design on different consumer groups and product categories. The study provides insights for marketers and designers aiming to capture the attention of Generation Z consumers through strategic packaging design.